An Analysis of The Impact of Abundant Circulation of Porn VCD - Sri Pangestuti (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2009)
The research was entitled: Analysis to the Impact of Abundant Circulation of Porn VCD (A descriptive Study among Adolescents in Sub-province of Banyumas). This research was backgrounded on the existing problem that circulation of porn VCD could not be blocked. This condition was supported by the progress of communication technologies, such as internet and sophisticated cellular phones. Method used in this research was a descriptive qualitative with purposive sampling technique. The informants consisted of children that became victims of sexual crimes, adolescents who committed sexual crimes, distributors, tradesmen of porn VCDs, Binamitra NGO and Head of Crimes Division of Polres Banyumas, Head of Sub-section Prosecuting Attorney and her staffs. Research result indicates that (1) looking on porn VCD became a choice that was refreshing; (2) many sexual crimes had been conducted by mature damage of the nation (3) the circulation of porn VCD gave contribution to morality damage of the nation (4) inconsistence of the regulation executions were caused by business factors (5) raid by the police was not intensive and (6) such crime sanctions were still on light conditions, therefore the sexual crime actors do not discourage as well. Keywords: circulation, porn VCD, sexual crim